A study on removal of cutting oil from wastewater by using agricultural wastes. (2020) - Kaur, Simran; Sodhi, Amanpreet Kaur
Abstract: Cutting fluids or Metal Working fluids (MWFs) are used in metal-cutting and metal – working operations for lubrication and for reducing heat and friction between the cutting tool and workpiece. Disposal of MWFs creates high - volume waste streams which can lead to a high pollution load on treatment systems in addition to becoming a rearing ground for bacteria that produce rancid odors. Inappropriate disposal techniques of MWFs leads to contamination of air, water and soil. Amongst the various techniques recommended for treatment of oily wastewater, adsorption has been proven to be a pragmatic alternative. This batch study explores the adsorption capability of ligno-cellulosic straws - Wheat Straw and Rice Straw by developing a UV–Visible Spectrophotometer technique for the determination of concentration of cutting oil in laboratory prepared samples. The samples were tested for varying dosage of adsorbents, contact time, pH and mixing speed. The ligno-cellulosic biomasses showed positive results when utilized with no modification. At similar initial oil concentrations, the adsorption capacity of rice straw was slightly more than that of wheat straw, the values being 66.127% and 63.215% respectively. Outcomes of the experiments proved that adsorption kinetics follows Langmuir isotherms with the maximum amount of oil being adsorbed on wheat straw being 0.588 g/g and 0.667 g/g for rice straw.